Immune monitoring and risk of infection in pediatric liver transplantation: a prospective study - Cuesta-Martín de la Cámara, Ricardo; Miguel-Berenguel, Laura; Cámara, Carmen; Losantos-García, Itsaso; Frauca-Remacha, Esteban; Hierro-Llanillo, Loreto; Muñoz-Bartolo, Gema; Lledín-Barbacho, María Dolores; Martínez-Feito, Ana; López-Granados, Eduardo; Sánchez-Zapardiel, Elena (Frontiers in Immunology, 2025)
BackgroundImmune monitoring has been proposed to optimize immunosuppressive therapy in liver recipients. This study aims to describe immunological changes following liver transplantation in pediatric recipients and to identify immune markers associated with post-transplant complications.MethodsThe immunological status of 95 pediatric liver recipients was prospectively assessed before transplantation and at 1, 3, 6, 9 and 12 months post-transplantation. Serum immunoglobulins (Ig) were measured by nephelometry and immunophenotype was evaluated by flow cytometry. T, B and NK lymphocyte counts were adjusted for age using standard reference ranges.ResultsGraft rejection, post-transplant lymphoproliferative disorder and autoimmune hepatitis was diagnosed in 6%, 2% and 0% patients, respectively. Early infections affected 43% patients, while late infections occurred in 17%, 24%, 10% and 9% recipients at each follow-up interval. Baseline immune dysregulation primarily involved the cellular compartment, with 78% recipients showing lymphopenia. Lymphocyte subpopulation scores improved following liver transplantation, with CD4+ score normalizing by month 1 and CD8+, CD19+ and NK scores by month 6. First-month IgG hypogammaglobulinemia, observed in 20% recipients, resolved completely at month 12. First-month T-cell lymphopenia (CD3+ hazard ratio [HR] 2.48, p=0.005; CD8+ HR 2.38, p=0.008) and hypogammaglobulinemia (IgG HR 2.18, p=0.036; IgA HR 2.40, p=0.011; IgM HR 2.61, p=0.006) were associated with higher risk of late infections. In multivariate analysis, only CD3+ T-cell lymphopenia remained a significant predictor (HR 2.13, p=0.030).ConclusionsBaseline immune dysregulation resolved within the first months post-transplantation. Early infections were unrelated to immune markers, while late infections were associated with CD3+ T-cell lymphopenia and hypogammaglobulinemia.